Effects of intermittent hypoxia on running economy - Burtscher, M.; Gatterer, H.; Faulhaber, M.; Gerstgrasser, W.; Schenk, K. (International Journal of Sports Medicine, 2010)
We investigated the effects of two 5-wk periods of intermittent hypoxia on running economy (RE). 11 male and female middle-distance runners were randomly assigned to the intermittent hypoxia group (IHG) or to the control group (CG). All athletes trained for a 13-wk period starting at pre-season until the competition season. The IHG spent additionally 2 h at rest on 3 days/wk for the first and the last 5 weeks in normobaric hypoxia (15-11% FiO2). RE, haematological parameters and body composition were determined at low altitude (600 m) at baseline, after the 5th, the 8th and the 13th week of training. RE, determined by the relative oxygen consumption during submaximal running, (-2.3±1.2 vs. -0.3±0.7 ml/min/kg, P<0.05) and total running time (+1.0±0.9 vs. +0.4±0.5 min, P<0.05) changed significantly between the IHG and CG only during the first 5-wk period. Haematological and cardiorespiratory changes indicate that the improved RE was associated with decreased cardiorespiratory costs and greater reliance on carbohydrate. Intermittent hypoxia did not affect RE during the second 5-wk period. These findings suggest that the effects of intermittent hypoxia on RE strongly depend on the training phase.